Fungsi Instagram sebagai Sarana Komunikasi Politik Raden Muhammad Khalil Prasetyo - Nasution, Dinda Faridha; Rambe, Uqbatul Khoir; Damanik, Agusman (ANWARUL, 2024)
Among the politicians who utilize social media to communicate about politics is Raden Muhammad Khalil Prasetyo. This political message is intended at his supporters, the residents of Medan City. Political players can draw in voters, engage in direct communication with the public, and have private discussions with them using social media. This study attempts to identify the political communication patterns on Instagram of Raden Muhammad Khalil Prasetyo and the advantages that he derives from using the platform. Using descriptive qualitative research techniques, this study looks at how to use the data collected to address current issues. This essay presents, examines, interprets, and conducts direct interviews with informants as the key data source for the author. The study's findings demonstrate that a politician must talk gently and courteously while interacting with the general populace. The people will view the politician favorably as a result of this. You need Instagram management abilities to make a favorable impression, such publishing videos of engaging activities rather than dull ones. He needs to make the most of Instagram's features to grow his following and make it easier for others to communicate with him.